Model Predictive Control-Based Voltage Oscillations Stabilizer for Point-of-Load Converter With EMI Filter in DC Microgrids - Kumar, Ranjan; Bhende, Chandrashekhar N. (IEEE journal of emerging and selected topics in industrial electronics (Print), 2025)
Power to the ac loads in a dc microgrid is mostly provided by point-of-load (POL) converters with integrated input LC filters. However, the interaction between the LC filter and POL converters may introduce instability and voltage oscillations across input dc capacitor. To address this issue, this article proposed an active damping stabilization control by incorporating a dc-side control stabilizing term into the finite control set model predictive control (FCS-MPC) algorithm. A new cost function is proposed in FCS-MPC control. The proposed method improves transient response and mitigates the voltage oscillations. Moreover, the proposed method requires fewer current sensors compared to alternative approaches, ensuring stability through an intrinsic and precise control strategy. Experimental and simulation results validate the effectiveness of the proposed stabilization control, offering a promising solution for POL converter applications.